Polyimide‐Based Flexible Plasma Sheet and Surface Ionization Waves Propagation. (19th August 2021) - Sun, Yuhao; Zhang, Bo; Wang, Chenxu; Zhang, Guanjun
Abstract: Surface discharges on flexible substrates are attracting attention for their unique capability to generate large‐scale non‐thermal plasma and potential adaptability to complex objects in many fields, like biomedical inactivation and material processing. Two fundamental issues are manufacture of stable flexible plasma sources and mechanism of multiple surface ionization waves (SIWs) propagation on curved gas‐solid interfaces. A polyimide‐based flexible plasma sheet is realized through printed circuit board with a non‐exposed electrode structure for discharge and the propagation properties of SIWs along its surface are investigated by experiments and simulations. Results show that SIWs start near the high‐voltage electrodes, and develop to the ground electrodes in a symmetrical petal pattern shaped by the potential gradient. The counter‐propagating SIWs merge above the ground electrodes, as the electrons' distribution converts from filament channel to a diffuse spatial distribution. Furthermore, bending the flexible sheet can change the charge density above the surface of polyimide, thus affects the space electron number density and electron temperature, but does not influence the overall appearance of SIWs propagation. This work will not only help to understand the surface process of ionization waves, but also benefit further researches on the application of flexible‐material‐based plasma source. Abstract : A polyimide‐based flexible sheet to generate non‐thermal plasma in atmosphere is realized and the propagation of ionization waves along its surface is studied. Multiple waves propagate in a petal pattern, which is impervious to different curvature of the sheet. Bending the flexible plasma sheet will not significantly affect its utility in the fields of material processing and biomedical application.